Implementation of Reliability Centered Maintenance Method for the Main Engine of Tugboat X to Select the Maintenance Task and Schedule - Dwi Priyanta; Nurhadi Siswantoro; Madina Nur Pratiwi (Institut Teknologi Sepuluh Nopember, 2020)
Tugboat is the supporting system that plays an essential role in port. A tugboat used for maneuvering, primarily pulling or pushing bigger vessel in open seas or river to be able to lean in port. PT.X known as a company has a prominent business field in provides such as tugboat. On the PT. X Annual Report of 2018 reported several cases that caused that related to the reliability of the main engine. The failure occurred on the main engine, affected commission days targeted was not achieved. Reliability-Centered Maintenance (RCM) is a maintenance method that focused on elevating the reliability of a component in the system(s). RCM used a risk management principle to determine the maintenance task and schedule appropriately. RCM process implemented using the Guide for Survey Based on Reliability-Centered Maintenance (RCM) by the American Burau of Shipping (ABS). Based on the results of this research, there were 38 task list type which is obtained based on the analysis of maintenance task allocation and planning. The percentage of maintenance types from each failure mode (task type) Preventive Maintenance (PM) is 29%, Condition Monitoring (CM) is 29%, Finding Failure (FF) is 21% and One-Time Change (OTC) is 21%. Work package for each interval is created from every failure mode for each interval for maintenance/inspection.